Analisis Etika Bisnis Islam dalam Penetapan Harga Keseimbangan Pasar Berdasarkan Pemikiran Ibnu Khaldun - Machrus, Ali; Asma, Khusnul; Munawaroh, Nur Laila Imas; Yunita, Ita (Al-Jadwa: Jurnal Studi Islam, 2023)
This research aims to analyze Islamic business ethics in determining market equilibrium prices based on Ibn Khaldun's thoughts. This research uses qualitative methods with data collection techniques through documentation techniques, observation and interviews with informants. Based on the research results, it can be concluded that at different levels, traders with small capital tend to have poor moral values such as cheating, playing with the scales, and playing with prices. Buyers tend to suffer losses and experience fraud in buying and selling. Meanwhile, the current market price determination is not based on the theory of demand and supply, but the price is high because the price is taken from the agent where the trader takes the merchandise, the seller only adjusts the price and on the other hand the high demand is caused by the behavior of certain individuals or middlemen who cheat by hoarding goods with the aim of taking advantage of the scarcity of supply by raising the price of goods above the normal price when many goods are needed.